A survey of complex trauma in families who have children and adults who have a learning disability and/or autism. Issue 5 (6th September 2021) - Baker, Peter; Cooper, Vivien; Tsang, Winnie; Garnett, Isabelle; Blackman, Noelle
Abstract : Purpose: There is an established literature supporting the idea that families who have children and adults who have a learning disability and/or autism have a greater vulnerability to mental health problems or poor psychological health. There are shortcomings in this literature in that there is a little consideration of the impact the families interaction with services has on their well-being. It is argued that complex post-traumatic stress disorder (CPTSD), with its focus on prolonged chronic exposure to trauma experiences and the recognition that this can occur in adulthood, may well be an appropriate framework to enable a better understanding of the experiences of families. Design/methodology/approach: A total of 214 family members completed a co-produced online survey in relation to potential traumatic events, impacts and support. Findings: The experiences of family carers of children and adults with a learning disability and/or who are autistic would appear to be multi-layered and complex, with many experiencing a wide range of traumatic events with the associated emotional and personal sequela. The reported responses are consistent with CPTSD with 10% of having received a diagnosis of PTSD. Their experience was that the system failed not only to provide support but also created additional trauma. Practical implications: A trauma-informed approach needs to be adopted by agencies and professionals that serve families to ensure they understand their potential contribution to the trauma families experience. Originality/value: To the best of the authors' knowledge, this is the first study that has attempted to examine the experience of families using the framework of CPTSD.